On the Octonionic Inclined Curves in the 8-Dimensional Euclidean Space - Bektas, Ozcan; Yuce, Salim (HINDAWI LTD, 2014)
We describe octonionic inclined curves and harmonic curvatures for the octonionic curves. We give characterizations for an octonionic curve to be an octonionic inclined curve. And finally, we obtain some characterisations for the octonionic inclined curves in terms of the harmonic curvatures.
Keywords: Engineering; Mathematics